2016
DOI: 10.1007/s00415-015-7905-2
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular migraine: the most frequent entity of episodic vertigo

Abstract: Vestibular migraine (VM) is the most common cause of episodic vertigo in adults as well as in children. The diagnostic criteria of the consensus document of the International Bárány Society for Neuro-Otology and the International Headache Society (2012) combine the typical signs and symptoms of migraine with the vestibular symptoms lasting 5 min to 72 h and exclusion criteria. Although VM accounts for 7 % of patients seen in dizziness clinics and 9 % of patients seen in headache clinics it is still underdiagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
146
0
28

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(198 citation statements)
references
References 85 publications
6
146
0
28
Order By: Relevance
“…It has lifetime prevalence of VM which was about 1% and 1-year prevalence of 0.9% in the general population [20]. Therefore, VM may be the most common cause of recurrent spontaneous vertigo attacks after benign paroxysmal positional vertigo (BPPV) [21]. Despite the relatively high prevalence of VM, it remains underdiagnosed.…”
Section: Epidemiology Of Vmmentioning
confidence: 99%
“…It has lifetime prevalence of VM which was about 1% and 1-year prevalence of 0.9% in the general population [20]. Therefore, VM may be the most common cause of recurrent spontaneous vertigo attacks after benign paroxysmal positional vertigo (BPPV) [21]. Despite the relatively high prevalence of VM, it remains underdiagnosed.…”
Section: Epidemiology Of Vmmentioning
confidence: 99%
“…[11] Magnetic resonance imaging studies report possible pathoanatomic connections between the pain and vestibular systems in migraine. [12] Another functional imaging study reported increased metabolism of the temporo-parietal-insular areas and bilateral thalami in two VM patients.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, VM was only added in the appendix of the ICHD-3 beta. Diversity of nomenclature and different diagnostic approaches, besides the intrinsic complexity of the diagnosis itself [37], led to the elaboration of consistent criteria, that could contribute to organize and homogenize VM clinical approach (see “ICHD-3 Beta Diagnostic Criteria of Vestibular Migraine”).…”
Section: Migraine Clinical Manifestationsmentioning
confidence: 99%
“…Drugs such as calcium-channel blockers, namely, flunarizine and cinnarizine, are popular in VM prophylactic treatment. Cinnarizine was tested in a retrospective, single-centre, open-label study on VM and migraine associated with vertigo, in 1993, in 24 patients [37]. The conclusion was that the drug was safe and effective in reducing both headache and vertigo aspects of “migraine plus vertigo” among patients who suffer from either VM or MBA associated with vertigo [96].…”
Section: Treatmentmentioning
confidence: 99%